2016
DOI: 10.1016/j.exer.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Diquafosol promotes corneal epithelial healing via intracellular calcium-mediated ERK activation

Abstract: Diquafosol is known as a purinergic P2Y2 receptor (P2Y2R) agonist that stimulates water and mucin secretion from conjunctival epithelial cells and goblet cells, leading to tear film stability in dry eye. However, its effect on corneal epithelial healing has not yet been elucidated. The aim of the present study was to evaluate the effect of diquafosol on corneal epithelial healing in vivo and on P2Y2R-related downstream signaling pathways in vitro. We administered 3% diquafosol ophthalmic solution on 3 mm-diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 54 publications
2
27
0
1
Order By: Relevance
“…They showed that topical administration of RvE1 significantly increased tear production and down regulates cyclooxygenase-2 (COX-2) expression, and increased the density of superficial epithelial cells in the dry-eyed mouse model [Li et al, 2010]. Diquafosol is reported to be beneficial in tear film stabilization and repair of corneal epithelial damages [Yarmola et al, 2007;Bremond-Gignac et al, 2014;Byun et al, 2016]. Diquafosol sodium and rebamipide.…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that topical administration of RvE1 significantly increased tear production and down regulates cyclooxygenase-2 (COX-2) expression, and increased the density of superficial epithelial cells in the dry-eyed mouse model [Li et al, 2010]. Diquafosol is reported to be beneficial in tear film stabilization and repair of corneal epithelial damages [Yarmola et al, 2007;Bremond-Gignac et al, 2014;Byun et al, 2016]. Diquafosol sodium and rebamipide.…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
“…This drug is a P2Y2 purinergic receptor agonist that stimulates the receptors in ocular tissues and thus increases mucin (conjunctival goblet cells stimulation) and the aqueous portion of tear film (conjunctival epithelial cells stimulation) [Shigeyasu et al, 2015]. Diquafosol is reported to be beneficial in tear film stabilization and repair of corneal epithelial damages [Yarmola et al, 2007;Bremond-Gignac et al, 2014;Byun et al, 2016].…”
Section: Medical Managementsmentioning
confidence: 99%
“…Interestingly, we observed this effect at a low concentration (2 mg/ml). Byun et al reported that the effect of diquafosol on corneal epithelial healing was accelerated at concentrations from 20 to 200 µM, but inhibited at concentrations over 2000 µM [23]. This concentration dependence might be related to BAC concentrations in diluted diquafosol, and that whereas diquafosol promotes corneal epithelial wound healing, BAC at higher concentration inhibits this process.…”
Section: Discussionmentioning
confidence: 99%
“…Diquafosol is a P2Y2 purinergic receptor agonist that stimulates the receptors in ocular tissues and thus increases mucin (conjunctival goblet cells stimulation) and the aqueous portion of tear film (conjunctival epithelial cells stimulation) [37]. Three percent diquafosol ophthalmic solution is effective for the treatment of dry eye disease through tear film stabilization and repair of corneal epithelial damages [38,39]. Another P2Y2 receptor agonist is uridine.…”
Section: Medical Managementsmentioning
confidence: 99%